2006
DOI: 10.2174/157018006776743242
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Channel Openers: The Case of BK Channel Activators

Abstract: Large-conductance calcium-activated potassium channels, also known as BK or Maxi-K channels, occur in many types of cells, where they play an essential role in the regulation of cell excitability and function. BK channel openers constitute a heterogeneous group of organic compounds being able to activate BK channels and having a wide therapeutic potential for the treatment of different neurological, urological and cardiovascular diseases. This review addresses the novel research on BK channels as drug targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…These results suggest that BK channel activators could represent a novel therapeutic approach for treating overactive bladder. However, despite the development of a large number of BK channel openers over the last two decades (23)(24)(25)(26)(27)(28)(29), they have failed to progress through clinical trials, because they showed poor efficacy, presumably due to their lack of effect at physiological membrane potentials, combined with a reduction in BK channels in patients with overactive bladder (30).…”
Section: +mentioning
confidence: 99%
“…These results suggest that BK channel activators could represent a novel therapeutic approach for treating overactive bladder. However, despite the development of a large number of BK channel openers over the last two decades (23)(24)(25)(26)(27)(28)(29), they have failed to progress through clinical trials, because they showed poor efficacy, presumably due to their lack of effect at physiological membrane potentials, combined with a reduction in BK channels in patients with overactive bladder (30).…”
Section: +mentioning
confidence: 99%
“…[6] Consequently, the pharmaceutical industry has invested significantly in trying to target smooth muscle function by developing novel BK channel modulators to help treat disorders such as urinary incontinence. [6][7][8][9][10] Although a large number of chemically diverse BK channel openers have already been developed, [8,9] only a few studies [11][12][13] have focused on examining the effects of these compounds across a wide voltage range to include physiological potentials (~−100 mV to 0 mV). [10][11][12] Instead, the majority of studies have focused on the ability of compounds to open channels only at potentials some 50 to 100 mV more positive than a cell is ever likely to encounter in vivo.…”
Section: Main Textmentioning
confidence: 99%
“…Thus, in cardiovascular diseases BK Ca channel modulation may have therapeutic benefits. BK Ca blockers (Shieh et al 2007) may possibly constrict a dilated blood vessel whereas BK Ca openers (Nardi et al 2006) could dilate a constricted blood vessel as observed in the treatment of stroke. Dilatation of cerebral blood vessels is believed to be involved during a migraine attack (Ray and Wolff 1940) together with activation of the neurovascular pain pathway (Edvinsson and Uddman 2005;Goadsby et al 2002;Silberstein 2004).…”
Section: Introductionmentioning
confidence: 99%